2010
DOI: 10.1007/s13206-010-4204-y
|View full text |Cite
|
Sign up to set email alerts
|

Optical enzyme-linked immunosorbent assay on a strip for detection of Salmonella typhimurium

Abstract: A rapid and sensitive enzyme-linked immunosorbent assay (ELISA) on an immunochromatographic strip was evaluated for the measurement of Salmonella typhimurium. Two different optical signal generation methods (colorimetric and chemiluminescent) were used to develop the proposed immunostrip system. Colorimetric and chemiluminescent signals could be successfully generated using the proposed immunostrip system, and S. typhimurium could be quantitatively measured in the range of 9.2×10 3 to 9.2×10 6 CFU/mL within 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…A similar pattern was observed in a previous study. 10 The intensity at the capture region was analyzed with ImageJ program and plotted as shown in Figure 5(c). The plot shows that there is no increase in the signal during antigen binding (the first 6 min).…”
Section: -5mentioning
confidence: 99%
“…A similar pattern was observed in a previous study. 10 The intensity at the capture region was analyzed with ImageJ program and plotted as shown in Figure 5(c). The plot shows that there is no increase in the signal during antigen binding (the first 6 min).…”
Section: -5mentioning
confidence: 99%
“…The proposed immunostrip sensor system has the following advantages over the currently used immunosensors: a relatively low detection limit, costeffectiveness, ease of use, ease of manufacture, and inexpensive instruments. In our previous works 17, 18 , a simple immunostrip sensor system for the detection of single target pathogens was developed by using colourimetric and chemiluminescent signal generation methods. In this study, the previously developed immunostrip assay method was expanded to be used for the simultaneous and multiplex detection of four different pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, these methods have drawbacks, such as low sensitivity and high cost of instruments [13][14][15][16] . To overcome these drawbacks, we have developed a highly sensitive, cheap, and easy-to-use immunochromatographic ELISA assay method 17,18 . In previous studies, enzyme (horseradish peroxidase; HRP) was used as a labelling agent to amplify colourimetric and chemiluminescent signals.…”
Section: Introductionmentioning
confidence: 99%
“…Among the foodborne pathogens related to poisoning, Salmonella is reported to be the leading cause of poisoning in many countries including China [3,4]. Salmonella is a genus of Gram-negative bacteria that has more than 2000 pathogenic serotypes including the well-known serotypes S. typhimurium and S. enteritidis [5,6]. The main antigens of Salmonella are lipopolysaccharide (O antigen), flagellin (H antigen), and capsular polysaccharide (Vi antigen).…”
Section: Introductionmentioning
confidence: 99%
“…Some immunochromatographic strip assays based on serotype specific or serogroup specific mAbs have been used to detect common Salmonella strains including S. typhimurium [6,27,28], S. enteritidis [29], S. choleraesuis [30] and S. typhi [31]. Bautista et al [32] reported the detection of 19 out of 22 tested Salmonella strains using a commercial immunochromatographic strip.…”
Section: Introductionmentioning
confidence: 99%